What is Well-being? - William TOV, (Institutional Knowledge at Singapore Management University, 2023)
Well-being refers to all the ways one can evaluate and experience life positively. SMU Associate Professor of Psychology William Tov and his collaborators identified eight key findings about well-being and reviewed the evidence from research in psychology and a variety of other disciplines.